Direct cosmological inference from three-dimensional correlations of the Lyman α forest. Issue 2 (15th November 2022) - Gerardi, Francesca; Cuceu, Andrei; Font-Ribera, Andreu; Joachimi, Benjamin; Lemos, Pablo
ABSTRACT: When performing cosmological inference, standard analyses of the Lyman α (Ly α) three-dimensional correlation functions only consider the information carried by the distinct peak produced by baryon acoustic oscillations (BAO). In this work, we address whether this compression is sufficient to capture all the relevant cosmological information carried by these functions. We do this by performing a direct fit to the full shape, including all physical scales without compression, of synthetic Ly α autocorrelation functions and cross-correlations with quasars at effective redshift z eff  = 2.3, assuming a DESI-like survey, and providing a comparison to the classic method applied to the same data set. Our approach leads to a $3.5{{\ \rm per\ cent}}$ constraint on the matter density ΩM, which is about three to four times better than what BAO alone can probe. The growth term f σ8 ( z eff ) is constrained to the $10{{\ \rm per\ cent}}$ level, and the spectral index n s to $\sim 3-4{{\ \rm per\ cent}}$ . We demonstrate that the extra information resulting from our 'direct fit' approach, except for the n s constraint, can be traced back to the Alcock–Paczynski effect and redshift space distortion information.